Obedience to Law - Fernández García, Eusebio (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The obligation to obey the Law is shown as a kind of political liability and, in the last term, of moral liability. This is a selective obligation (neither absolute nor universal) and depends of Law’s justice.